Effectiveness of Digital Interventions in Improving Knowledge and Attitudes of Adolescent Mental Health: A scoping review - Nunung Wulandari; Apoina Kartini; Cahya Tri Purnami (Publikasi Indonesia, 2025)
Adolescent mental health is a critical issue that affects their quality of life and development. Digital interventions offer an innovative solution to enhance mental health literacy among adolescents. This article to identify the effectiveness of digital educational interventions in improving adolescents' knowledge and attitudes toward early detection of mental health issues. A scoping review was conducted using the PEOS framework. Literature searches were performed in PubMed and ScienceDirect databases for articles published between 2019 and 2024. A total of 15 articles were selected based on inclusion and exclusion criteria. Digital interventions, such as school-based applications and social media campaigns, enhanced mental health literacy and reduced stigma related to mental health. Several interventions also improved adolescents' abilities to recognize mental health symptoms and encouraged help-seeking behaviors. However, challenges such as low digital literacy and limited access remain significant barriers to implementation. Digital education effectively improves adolescents' knowledge and attitudes toward early detection of mental health issues. Culturally relevant approaches and stakeholder support are crucial for the program's sustainability.